The Method for Evaluating Cross-Shore Migration of Sand Bar under the Influence of Nonlinear Waves Transformation - Shtremel, Margarita; Saprykina, Yana; Ayat, Berna (MDPI, 2022)
Sand bar migration on the gently sloping sandy bottom in the coastal zone as a result of nonlinear wave transformation and corresponding sediment transport is discussed. Wave transformation on the intermediate depth causes periodic exchange of energy in space between the first and the second wave harmonics, accompanied by changes in the wave profile asymmetry. This leads to the occurrence of periodical fluctuations in the wave-induced sediment transport. It is shown that the position of the second nonlinear wave harmonic maximum determines location of the divergence point of sediment transport on the inclined bottom profile, where it changes direction from the onshore to the offshore. Such sediment transport pattern leads to formation of an underwater sand bar. A method is proposed to predict the position of the bar on an underwater slope after a storm based on calculation of the position of the maximum amplitude of the second nonlinear harmonic. The method is validated on the base of field measurements and ERA 5 reanalysis wave data.
Keywords: nonlinear wave transformation; coastal zone; sand bars; cross-shore sediment transport; VARIABILITY; MODEL; Environmental Sciences & Ecology; Water Resources